PENGARUH MODAL MANUSIA DAN MODAL PELANGGAN TERHADAP KINERJA YANG DIRASAKAN PETANI - Ryan Elfahmi; Ali Zaenal Abidin; Andi Sopandi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of human capital and customer capital on the perceived performance of farmers. The question in this study is whether human capital affects the perceived performance of farmers and whether customer capital affects the perceived performance of farmers. The analysis technique in this research includes correlation test, determination test and F test which is a model feasibility test, followed by multiple linear regression analysis and hypothesis testing (t). The sample method uses purposive sampling, with several criteria developed previously. Questionnaires were used to collect data from respondents. Respondents in this study were farmers in Blubur Limbangan District, Garut Regency. In total there are 356 respondents. Based on the results of hypothesis testing (t), human capital affects the perceived performance of farmers and customer capital affects the perceived performance of farmers.